Optic Neuritis–Independent Retinal Atrophy in Neuromyelitis Optica Spectrum Disorder. Issue 1 (March 2022) - Filippatou, Angeliki G.; Vasileiou, Eleni S.; He, Yufan; Fitzgerald, Kathryn C.; Kalaitzidis, Grigorios; Lambe, Jeffrey; Mealy, Maureen A.; Levy, Michael; Liu, Yihao; Prince, Jerry L.; Mowry, Ellen M.; Saidha, Shiv; et al.
Abstract : Background: A limited number of studies have investigated the presence of ongoing disease activity independent of clinical relapses in neuromyelitis optica spectrum disorder (NMOSD), and data are conflicting. The objective of our study was to examine whether patients with aquaporin-4 (AQP4)-IgG seropositive NMOSD exhibit progressive retinal neuroaxonal loss, independently of optic neuritis (ON) attacks. Methods: In this single-center, longitudinal study, 32 AQP4-IgG+ NMOSD patients and 48 healthy controls (HC) were followed with serial spectral-domain optical coherence tomography and visual acuity (VA) assessments. NMOSD patients with ON less than 6 months before baseline were excluded, whereas data from patients with ON during follow-up were censored at the last visit before ON. VA worsening was defined as a decrease in monocular letter acuity ≥5 letters for high-contrast VA and ≥7 letters for low-contrast VA. Analyses were performed with mixed-effects linear regression models adjusted for age, sex, and race. Results: The median follow-up duration was 4.2 years (interquartile range: 1.8–7.5). Relative to HC, NMOSD eyes had faster peripapillary retinal nerve fiber layer (pRNFL) (β = −0.25 µm/year faster, 95% confidence interval [CI]: −0.45 to −0.05, P = 0.014) and GCIPL thinning (β = −0.09 µm/year faster, 95% CI: −0.17 to 0, P = 0.05). This difference seemed to be driven by faster pRNFL and GCIPL thinning in NMOSD eyes without a history of ON compared with HC (GCIPL: β = −0.15 µm/year faster; P = 0.005; pRNFL: β = −0.43 µm/year faster, P < 0.001), whereas rates of pRNFL (β: −0.07 µm/year, P = 0.53) and GCIPL (β = −0.01 µm/year, P = 0.90) thinning did not differ between NMOSD-ON and HC eyes. Nine NMOSD eyes had VA worsening during follow-up. Conclusions: In this longitudinal study, we observed progressive pRNFL and GCIPL atrophy in AQP4-IgG+ NMOSD eyes unaffected by ON. These results support that subclinical involvement of the anterior visual pathway may occur in AQP4-IgG+ NMOSD.